Educação Física escolar e esportes náuticos: uma experiência pedagógica - Cruz, Randley Rayed de Castro (2023)
This research starts from the observation of the reality of a municipal and peripheral public school in Vitória, Espírito Santo, where the researcher acted as a Physical Education teacher. During the participatory planning for the 2021 school year, it was diagnosed that most students in the final years of elementary school reported not knowing, having no previous experience and not having curiosities about nautical sports, even though the city in which they lived figured as one of the main Brazilian nautical centers. On that occasion, the researcher realized that many of them were not in the habit of going to the beach and some claimed to not even know the sea. This diagnosis instigated an action-research that sought to situate nautical sports and aquatic adventure body practices as content of the Physical Education discipline, as well as to reflect and intervene on the barriers that limited students' access to these activities in their city, the order to produce sense and significance for them. 20 didacticpedagogical interventions were developed with an eighth grade class, in which nautical sports were addressed in the curricular course of Physical Education in the year 2022. The interventions included games with the theme of nautical sports, movement simulation, construction of toys, visits to a swimming pool and the beach to experience kayaking, stand up paddle and sailing and the organization of a school festival, among other initiatives. It was evaluated that the didactic unit contributed for the students not only to know and experience part of these activities, but also allowed them to produce meanings about them, establishing a rich set of relationships with the modalities, their equipment, the aquatic environment and the city where they live. It also became evident that, although this is a difficult topic to develop in the school context, there are possibilities and viable alternatives for Physical Education teachers to approach it.